Digital Preservation and Promotion: Evaluating the Impact of Virtual Museums on the Traditional Art of Rural Areas. - Ping, Yu An; Zheng, Xu (Journal of Arts Management, Law & Society, 2024)
This study aimed to assess the effectiveness of interactive technologies in preserving and disseminating traditional art of rural areas in China during the digital era. The study also found that more than 70% of participants acknowledged the positive impact of the virtual museum on interest and enthusiasm for Chinese traditional art of rural areas. Regarding the age dynamics of the perception of the "China RurArt" museum, the following trends were identified: the 18–25 age group showed high perception and increased interest after visiting; the 26–35 age group focused on tradition preservation and expressed high satisfaction with convenience; the 36–45 age group demonstrated a positive attitude and plans for repeat visits; the 46–55 age group expressed support for the idea of preserving cultural heritage with a high level of satisfaction; participants over 55 years old acknowledged the role in tradition preservation with a high evaluation of the museum's user-friendliness.